Economic resilience with an exchange peg : the Barbados experience, 1985-2000 - Worrell, DeLisle...[et al.] (IMF [Washington]US, 2003)
Discusses the institutional arrangements for exchange rate targeting in Barbados and the critical role they played in the policy response to its balance of payments crisis of 1991-92.